Learning modulation by endogenous hippocampal IL-1: blockade of endogenous IL-1 facilitates memory formation. - Depino, A; Alonso, M; Ferrari, C; del Rey, A; Anthony, D; Besedovsky, H; Medina, J; Pitossi, F (2004)
The interleukin-1 (IL-1) cytokine family (IL-1alpha, IL-beta, and the IL-1 receptor antagonist) is involved in immune and inflammatory responses both in the brain and in the periphery. Recently, it has also been shown to influence behavior and memory consolidation. However, within the experimental systems studied, it has remained unclear whether the role of IL-1beta is associated solely with a pathophysiological process or whether it is a neuromodulator in normal adult brain. To evaluate the involvement of the nonpathological endogenous IL-1 system in learning, we studied the expression of IL-1alpha, IL-1beta, and IL-1ra during memory consolidation. We observed a learning-specific hippocampal IL-1alpha mRNA induction, but not that of IL-1beta or IL-1ra mRNAs, after inhibitory avoidance training. Moreover, when IL-1 receptor activity was inhibited using an adenoviral vector that expresses the IL-1 receptor antagonist (IL-1ra) in the hippocampus, both short-term and long-term memory retention scores were facilitated. In contrast, endogenous hippocampal IL-1 played no role in the habituation to a novel environment. These results demonstrate that endogenous hippocampal IL-1 specifically modulates a fear-motivated learning task, and suggest that IL-1alpha activity in the CNS is part of the hippocampal memory processing.